On the Trail of Preparations - Loïc Riom; Mylène Tanferri (Revue d'anthropologie des connaissances)
This introduction aims to demonstrate how following the trail of preparations to act extends and enriches conceptually and empirically both theories of action and the anthropology of knowledge. Firstly, we distinguish preparations for action from planned action. To do so, we situate our interest in preparations within the works that, from the sociology of work to the study of organizations, have focused on plans, prescriptions, and the formation of habits. Secondly, drawing on the nine articles that compose this special issue, we outline five axes of reflection: preparations as getting embedded in the field; the relationship with the unexpected; the knowledge of preparations; preparations' devices; and the collectives that preparations contribute to (trans)form.